Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Yumi  San
Xem chi tiết
Yumi  San
Xem chi tiết
Pham Ngoc Anh
Xem chi tiết
JuliaB
Xem chi tiết
ILoveMath
25 tháng 2 2022 lúc 10:26

\(A=\dfrac{5}{11}.\dfrac{5}{7}+\dfrac{5}{11}.\dfrac{2}{7}+\dfrac{6}{11}=\dfrac{5}{11}\left(\dfrac{5}{7}+\dfrac{2}{7}\right)+\dfrac{6}{11}=\dfrac{5}{11}.1+\dfrac{6}{11}=\dfrac{5}{11}+\dfrac{6}{11}=\dfrac{11}{11}=1\)

\(B=\dfrac{3}{13}.\dfrac{6}{11}+\dfrac{3}{13}.\dfrac{9}{11}-\dfrac{3}{13}.\dfrac{4}{11}=\dfrac{3}{13}\left(\dfrac{6}{11}+\dfrac{9}{11}-\dfrac{4}{11}\right)=\dfrac{3}{13}.1=\dfrac{3}{13}\)

\(C=\left(\dfrac{12}{16}-\dfrac{31}{22}+\dfrac{14}{91}\right)\left(\dfrac{1}{2}-\dfrac{1}{3}-\dfrac{1}{6}\right)=\left(\dfrac{12}{16}-\dfrac{31}{22}+\dfrac{14}{91}\right)\left(\dfrac{3}{6}-\dfrac{2}{6}-\dfrac{1}{6}\right)=\left(\dfrac{12}{16}-\dfrac{31}{22}+\dfrac{14}{91}\right).0=0\)

Vũ Minh Hằng
Xem chi tiết
Quay Cuồng
13 tháng 3 2017 lúc 21:30

A=\(\frac{6}{19}\)\(\frac{-7}{11}\)+\(\frac{6}{19}\).\(\frac{-4}{11}\)+\(\frac{-13}{19}\)

  =\(\frac{6}{19}\).(\(\frac{-7}{11}\)+\(\frac{-4}{11}\))+\(\frac{-13}{19}\)

 =\(\frac{6}{19}\).\(\frac{-11}{11}\)+\(\frac{-13}{19}\)

  =\(\frac{6}{19}\).-1 +\(\frac{-13}{19}\)

=\(\frac{-6}{19}\)+\(\frac{-13}{19}\)

=\(\frac{-19}{19}\)

+1

Quay Cuồng
13 tháng 3 2017 lúc 21:31

=1  nhầm

Dương Nghiên Đình
Xem chi tiết
Nguyễn Minh Ngọc
Xem chi tiết
Nguyễn Bảo Châu
Xem chi tiết
Nguyen Sy Hoc
27 tháng 7 2018 lúc 6:07

A)6 và 4/5-(1 và 2/3+3 và 4/5)

=6+4/5-1-2/3-3-4/5

=(6-1-3)+(4/5-4/5)-2/3

=2-2/3=1 và 1/3

B)[(19+5/8/7/12)-(13+1/4/7/12)]X4/5

=[(19-13)+(5/8/7/12-1/4/7/12)]X4/5

=[6+3/8/7/12]X4/5

=[6+9/14]X4/5

=93/14 X4/5=186/35

nhớ

Dương Nghiên Đình
Xem chi tiết
Trinh Song Thu
1 tháng 5 2021 lúc 22:56

-3/11.(-22)/66.121/15

=(-3).(-22).121

 11.66.15

=11

15

3/7.2/5.7/3.20.19/72

=3.2.7.20.19

7.5.3.72

=76

16

6/7.8/13+6/13.9/7-3/13.6/7

=6/7.8/13+6/7.9/13-3/13.6/7

=6/7.(8/13+9/13-3/13)

=6/7.14/13

=12/13

-1/4.152/11+68/4.(-1)/11

=152/4.(-1)/11+68/4.(-1)/11

=(-1)/11.(152/4+68/4)

=(-1)/11.220/4

=-110/22

-5/7.2/11+(-5)/7.9/11+12/7

=-5/7.2/11+-5/7.9/11+12/7

=-5/7.(2/11+9/11)+12/7

=-5/7.1+12/7

=(-5)/7+12/7

=7/7

=1

146/13-(18/7+68/13)

=146/13-18/7-68/13

=(146/13-68/13)-18/7

=78/13-18/7

=6-18/7

=42/7-18/7

=24/7

Khách vãng lai đã xóa